THE PATTERNS OF ETHNOBOTANY OF WILD MEDICAL PLANTS IN WESTERN BALKAN (SE EUROPE) - Redzic, Sulejman (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Results of ethnobotanical research provide answers to forms of ethnogenesis of certain ethnical groups, as well as applicable forms of anthropogenesis [1]. The Balkan Peninsula area was for years a stage where cultures and civilizations of East and West collided [2]. Along with floristic richness, this area developed different forms of use of wild plants in traditional medicine [3]. Using method of ethnobotanical interview (455 adults, age between 50 – 93) it was determined that about 700 species of plants were used in traditional medicine in this territory, which is almost 10 % of total flora of this area. About 150 species are used in Mediterranean areas for preparation of traditional mixtures (tinctures in grape brandy or wine), aromatic alcoholic beverages and lotions based on rosin used in treatment of stomach, respiratory, heart and skin diseases. About 50 plant species growing in difficult mountain conditions are used in preparation of infusions, tinctures in plum brandy, and different lotions used in treatment of chronic stomach, respiratory, heart, skin and other diseases, and in treatment of child diseases. The level of use of wild flora in traditional medicine of people in western Balkan is in correlation with floristic richness, climate, social – economic circumstances, isolation of ethnic groups and difficult natural conditions. Certain differences in preparation of medicines are also determined in different ethnic groups.